Assessment of the feasibility of SP-10 as a male fertility marker and validation of a lateral flow immunoassay for indirect sperm concentration analysis - Mowla, Shahriar (2018)
Over the past few decades, the emphasis on male gamete has increased as male factor infertility contributes to almost 30% of infertile couples. As a result, the need for development of more accurate assays is now more important than ever. Determination of the concentration of sperm using an indirect assay does not possess the inherent user subjectivity, procedure uncertainty and biological restrictions such as viscosity of manual semen analysis. This thesis aims to assess the feasibility of SP-10 protein to be used as a fertility marker by the assessment of a lateral flow immunoassay.